The Image of China Constructed by Foreign Self-Media: An Approach to Popular Narrative in the YouTube Channel “Jabiertzo” - Xiang, Chen; Jiayu, Shen (Sinología hispánica. China Studies Review, 2026)
With the increase in international exchanges, the foreign public is eager to get close to the real China, especially the “popular narratives” that involve the daily life of ordinary people. This study investigates the “Jabiertzo” channel on YouTube to reflect on how foreign self-media can counteract these distortions from the perspective of “the Other”. Using “semantic network analysis”, it is revealed that, unlike official and dominant media, these media focus more on personal experiences of daily life, accurately reflecting the changes in Chinese society and fostering a deeper understanding. This work explores how to use the shared emotional values between different cultures to improve the interaction and sensory experience of the international public, contributing to a more vivid and multidimensional narrative of China.